IN PUBLIC HEALTH WE TRUST: THE EXPERIENCES OF KAZAKHSTANI CITIZENS ON INTERPERSONAL AND INSTITUTIONAL TRUST IN PUBLIC HEALTHCARE SYSTEMS - Lopukhov, Alexandr (Nazarbayev University School of Sciences and Humanities, 2024)
This study explores trust in the healthcare context by analyzing interpersonal (patient=doctor) and institutional factors (patient=healthcare system). The study was conducted in Astana city in Kazakhstan among working-age adults (25-35 years old) during January 2024. In the scope of the research, trust is defined as a belief by the trustor (A) – patient, that an action (X) – medical treatment, will happen at some time (Y) in the future by the trustee (B) – the doctor/healthcare system. This belief is based on some factors that make up the trustworthiness of the trustee (B). The findings reveal four interpersonal factors such as hostility of doctors, lack of contact with doctors, in-group trust and ineffective treatment. Also, three institutional factors were revealed – the lack of funding, the lack of health promotion and the mistrust in government. The correlation between institutional and interpersonal factors produced mixed results. Some participants believe that institutional trust arises from interpersonal and that doctors are the direct executors of the healthcare system, thus they must do their best to provide quality care in order to raise the institutional trust in the healthcare system. However, other participants claimed that doctors are the “prisoners” of the healthcare system, and that interpersonal trust arises from institutional, so the system must provide good conditions and infrastructure for the doctors in order to foster trust.
Keywords: public health; medicine; trust; interpersonal trust; institutional trust; doctor; healthcare; quality of healthcare; Type of access: Open Access